A Peanut Shell Inspired Scalable Synthesis of Three-Dimensional Carbon Coated Porous Silicon Particles as an Anode for Lithium-Ion Batteries. (20th February 2015) - Han, Xiang; Chen, Huixin; Liu, Jingjing; Liu, Hanhui; Wang, Peng; Huang, Kai; Li, Cheng; Chen, Songyan; Yang, Yong
Highlights: A novel, economical ball milling and heat treatment of porous silicon based anodes was introduced to boost the electrochemical performance of Li-ion batteries. The compact C/SiO2 -coated peanut shell-like electrodes could accommodate volume change effectively. The electrodes exhibited outstanding cycling performance and rate capacities. Our work gives a compelling look at a novel and large-scale production method of fabricating next generation Si/C anodes for high-performance LIBs. Abstract: A novel, economical ball milling and heat treatment of porous silicon based anodes was introduced to boost the electrochemical performance and cycle capacity of Li-ion batteries. The resultant peanut shell-like electrodes combined multiple advantageous features, including a continuous, flexible electrically conductive carbon network, a synergistic C/SiO2 coating layer and improved interfacial contact, in a peanut shell structure with void space. The electrodes achieved an initial discharge capacity of 1909 mA h g −1 with coulombic efficiency of 88.8% as well as a high reversible capacity of 1179 mA h g −1 after 120 cycles at 0.1C. In addition, the material was capable of reaching a capacity of 493 mA h g −1 even at the high charge rate of 4C. This work gives a compelling look at a novel and large-scale production method of fabricating next generation Si/C anodes for high-performance LIBs.